Rituximab in multiple sclerosis - Fatigue, cognition, and efficacy - Hellgren, Johan (Lund University, Faculty of Medicine Doctoral Dissertation Series, 2025)
Background: Multiple sclerosis (MS) is an inflammatory, demyelinating disease affecting the central nervous system. Fatigue and impaired information processing speed (IPS) are the most debilitating symptoms of MS. Natalizumab (NTZ) and rituximab (RTX), currently Sweden’s two most-prescribed drugs for MS treatment, are known to almost completely ameliorate clinical and radiological relapse activity in patients with RRMS. However, the effects on fatigue and IPS are unclear. RTX remains an offlabel therapy for MS. Methods: This thesis comprises two study designs. The first is a retrospective observational study evaluating the safety and efficacy of RTX in 83 patients with MS at the Helsingborg General Hospital. The second is a cross-sectional multicenter study including 128 patients with relapsing-remitting MS, treated with either NTZ or RTX for at least 24 months. Fatigue, IPS, and levels of the astrocyte marker, glial fibrillary acidic protein (GFAP), and axonal damage marker, neurofilament light (NfL), in the cerebrospinal fluid and plasma were compared in both treatment groups. IPS was assessed using the Symbol Digit Modalities Test (SDMT) and fatigue, with the Fatigue Scale for Motor and Cognitive Functions (FSMC). Fatigue and IPS were explored in relation to GFAP and NfL. Results: In the retrospective study, RTX significantly reduced relapses and new lesions on MRI. Serious adverse events were few. In the comparative cross-sectional study, no between-group differences were found regarding fatigue. Participants treated with NTZ performed significantly better on the SDMT than those treated with RTX. Plasma GFAP and NfL levels did not significantly differ between the treatment groups. Neither GFAP nor NfL exhibited significant associations with fatigue or IPS. Conclusion: RTX is a safe and effective option for treating relapsing-remitting MS. The significantly better performance on SDMT of patients treated with NTZ may have been influenced by repeated exposure to the test, i.e., practice effects. Longitudinal controlled studies are needed to further evaluate the effects of high-efficacy disease modifying therapies on fatigue and IPS in MS.
Keywords: Multiple sclerosis; Rituximab; Natalizumab; Fatigue; Information processing speed; GFAP; NFL; Oligocloncal bands; Kappa free light chain; Patient Reported Outcome Measures (PROMs)